The allure of sports in Western Culture - Zilcosky, John; Burks, Marlo A., 1986- (University of Toronto Press, 2019)
Sports are the most popular spectator events in the history of the world. This volume demonstrates how sports shape societies and individuals. The essays offer critical new insights and historical case studies from historians, theorists, literature scholars, and athletes.